El financiamiento y su relación con el Impuesto a la Renta de la Corporación Favorita - Pineda Gaona, Yaleni Gabriela (2024)
Financing is a financial strategy that helps companies to generate greater production and sales likewise, income tax is a tax that companies and individuals pay for developing their activities; the main objective of this research is to analyze financing and its relationship with income tax at Corporación Favorita. For its development, the financial statements and results of the Superintendencia de Compañías Valores y Seguros (Superintendence of Companies, Securities and Insurance) were used. Additionally, a bibliographic file was prepared, using a mixed descriptive and correlational approach, through the use of observation techniques and instruments such as the collection of bibliographic information. The financial analysis of Corporación Favorita helped analyze the main economic and financial factors. The economic factors analyzed were economic growth (GDP), inflation, and interest rates per deposit, which were beneficial for the company's productivity since it is solid and has the capacity to adapt to any economic scenario in the future. It was evidenced that the company has liquidity and solvency as well as a good management of financial resources. On the other hand, it was possible to identify that the financing with which the company works is internal, which corresponds to equity, and external, referring to financing from financial institutions. In addition, it was determined by means of the Spearman correlation coefficient and the p-values that the Log internal financing (p-value 0.018) and the Log external financing (p-value 0.016), showed values below the significance level (0.05), therefore, the alternative hypothesis was accepted. In the analysis carried out, it was concluded that there is a statistically significant relationship between internal and external financing and income tax.